Isolated Deep Infiltrating Endometriosis of the Sciatic Nerve: A Case Report and Overview of the Literature - Milena Zamurovic; Ana Tomic; Katarina Djordjevic; Sara Simanic; Jelena Sopta; Lukas Rasulic; Ljubica Simic; Jovan Jevtic; Olga Nedeljkovic-Arsenovic; Marija Rovcanin (Medicina, 2023)
Isolated deep infiltrating endometriosis (DIE) of sacral nerve roots or major pelvic nerves, including the sciatic nerve, is considered to be extremely rare. Due to the overlap with sciatica symptoms, the diagnosis of sciatica DIE is difficult yet crucial, as it results in permanent neural damage if left untreated. We report a case of a 45-year-old woman who experienced a three-year-long and recently exacerbating pain in her right leg, accompanied by a tingling sensation and weakness in her right leg and foot, with difficulty walking. In between regular menstrual bleedings, when her aforementioned symptoms worsened, she had been experiencing mild 10-day extra-cyclical bleeding. Her neurologist’s, orthopedist’s, and gynecological examinations were unremarkable. Magnetic resonance imaging (MRI) showed an infiltrative lesion on the right sciatic nerve that was immunohistochemically confirmed to be endometriosis. The patient was treated with gonadotropin-releasing hormone analogues (GnRHa), which led to a significantly diminished size of the lesion on the control MRI, and endometriosis remission was obtained. For persistent mild, but cyclical, pain and muscle weakness, continuous progestagnes were administered, with advice for physical therapy provided for her neuro-muscle rehabilitation and a scheduled check-up in 6 months.